2014
DOI: 10.1128/iai.01745-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Outer Membrane Lipoprotein Involved in Nasopharyngeal Colonization by Moraxella catarrhalis in an Animal Model

Abstract: Colonization of the human nasopharynx by Moraxella catarrhalis is presumed to involve attachment of this bacterium to the mucosa. DNA microarray analysis was used to determine whether attachment of M. catarrhalis to human bronchial epithelial (HBE) cells in vitro affected gene expression in this bacterium. Attachment affected expression of at least 454 different genes, with 163 being upregulated and 291 being downregulated. Among the upregulated genes was one (ORF113) previously annotated as encoding a protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Examination of data from a previous study that identified M. catarrhalis genes whose expression was upregulated when broth-grown bacteria were inoculated into the chinchilla nasopharynx (21) showed that there was little or no change in the level of mesR transcription, even though the levels of lipA and lipB transcripts increased approximately 4-fold and 1.5-fold, respectively. In M. catarrhalis bacteria that attached to human bronchial epithelial cells in vitro (80), there were very modest (i.e., 1.4-to 1.5-fold) increases in mesR, lipA, and lipB transcription levels. Further interpretation of the available regulatory data is limited by the fact that the phosphorylation, or a lack thereof, of a response regulator (i.e., MesR) greatly affects its ability to stimulate or inhibit transcriptional activity (81).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Examination of data from a previous study that identified M. catarrhalis genes whose expression was upregulated when broth-grown bacteria were inoculated into the chinchilla nasopharynx (21) showed that there was little or no change in the level of mesR transcription, even though the levels of lipA and lipB transcripts increased approximately 4-fold and 1.5-fold, respectively. In M. catarrhalis bacteria that attached to human bronchial epithelial cells in vitro (80), there were very modest (i.e., 1.4-to 1.5-fold) increases in mesR, lipA, and lipB transcription levels. Further interpretation of the available regulatory data is limited by the fact that the phosphorylation, or a lack thereof, of a response regulator (i.e., MesR) greatly affects its ability to stimulate or inhibit transcriptional activity (81).…”
Section: Discussionmentioning
confidence: 99%
“…Attachment assay. The ability of wild-type and mutant strains of M. catarrhalis to attach to an immortalized human bronchial epithelial cell line (16HBE14o-) (38) in vitro was measured as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations